Validity and reliability of the Tibetan version of s-EMBU for measuring parenting styles - Yangzong, Ciren (Psychol Res Behav Manag, 2016)
Parenting style experienced during childhood has profound effects on children’s futures. Scales developed in other countries have never been validated in the Tibetan context. The present study aimed to examine the construct validity and reliability of a Tibetan translation of the 23-item short form of the Egna Minnen Beträffande Uppfostran [One’s Memories of Upbringing] (s-EMBU) and to test the correlation between the parenting styles of fathers and mothers. A cross-sectional study was conducted in a sample of 847 students aged 12–21 years from Lhasa, Tibet, during September and October 2015 with a participation rate of 97.7%. The Tibetan translation of self-completed s-EMBU was administered. Confirmatory factor analysis was employed to test the scale’s validity on the first half of the sample and was then cross-validated with the second half of the sample. The final model consisted of six factors: three (rejection, emotional warmth, and overprotection) for each parent, equality constrained on factor loadings, factor correlations, and error variance between father and mother. Father–mother correlation coefficients ranged from 0.81 to 0.86, and the level of consistency ranged from 0.62 to 0.82. Thus, the slightly modified s-EMBU is suitable for use in the Tibetan culture where both the father and the mother have consistent parenting styles.